Penegakan Hukum Terhadap Kebakaran Hutan Guna Mengurangi Permasalahan Lingkungan Hidup di Indonesia - Susiyanti, Anissa; Emilia, Setyani Hilda; Kamal, Ubaidillah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The environment is a gift from God Almighty that we must take care of and preserve. The environment as a resource is an asset that can be needed for the welfare of society. But the problem of pollution and environmental damage in Indonesia is increasing day by day. Like the occurrence of forest fires, where forests are the lungs of the world. Forest fires can be caused by both natural factors and Human Factors. Forest fires also have an impact on all aspects of life, which causes pollution pollution that can have an impact on all living things. Therefore, there is a need for participation from the government and the community to deal with the problem of forest fires. This study aims to determine the law enforcement in Indonesia against forest fires that occur in Indonesia. This study uses descriptive qualitative research methods. This study discusses the effectiveness of law enforcement in handling forest fires in Indonesia and how efforts can be made to prevent forest fires in order to reduce environmental problems in Indonesia.